2007
DOI: 10.1080/10790268.2007.11753921
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models In Pressure Ulcer Research

Abstract: Background/Objective: Research targeting the pathophysiology, prevention, and treatment of pressure ulcers (PrUs) continue to be a significant priority for clinical and basic science research. Spinal cord injury patients particularly benefit from PrU research, because the prevalence of chronic wounds in this category is increasing despite standardized medical care. Because of practical, ethical, and safety considerations, PrUs in the human environment are limited to studies involving patients with pre-existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 34 publications
(22 reference statements)
0
40
0
Order By: Relevance
“…Deep Skin Ulcer and Change in Wound Surface Area Although various techniques for the creation of pressure ulcer animal models have been reported, [33][34][35] induction of the models is not necessarily easy; therefore, in this study, the deep skin ulcer was created by removing the full skin and subsequent freezing of the defective injury.…”
Section: Resultsmentioning
confidence: 99%
“…Deep Skin Ulcer and Change in Wound Surface Area Although various techniques for the creation of pressure ulcer animal models have been reported, [33][34][35] induction of the models is not necessarily easy; therefore, in this study, the deep skin ulcer was created by removing the full skin and subsequent freezing of the defective injury.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous animal models have been established in this research field17,20 for investigating various theories on etiological factors of PU formation, observing wound formation and healing, and assessing treatment modalities. Great progress has been achieved on PU animal research during the last 2 decades and precious knowledge has been acquired from these animal models, which has fostered the advances in recent PU basic research and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Many animal PU models have been developed to test different hypotheses in this field17,20 on several species, such as rat, dog, mouse, and pig. Although it is generally agreed that the pig is the ideal species for PU and wound healing research because of its fixed skin structure and cutaneous blood supply are similar to that in humans26, the most commonly used animals in PU research are rats and mice possibly due to their easy handling and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the previous in vitro findings (11,36), our results substantiated the potential role of apoptosis in deep tissue injury and have elaborated the corresponding apoptotic signaling pathways. In regard to the cellular death in pressure ulcer, it has been suggested that apoptosis may come before necrosis in the development of pressure ulceration although the topic of muscle apoptosis has not been systematically explored in pressure ulcer (26,35). Apoptosis is regulated by specific apoptotic factors that coordinate the sequential apoptotic events.…”
Section: Discussionmentioning
confidence: 99%